Directed energy deposition of CNTs/AlSi10Mg nanocomposites: Powder preparation, temperature field, forming, and properties. (July 2021) - Wan, Le; Shi, Shihong; Xia, Zhixin; Shi, Tuo; Zou, Yibo; Li, Kuan; Chen, Xiaming
Highlights: A preparation method of CNTs/AlSi10Mg composite powder for laser metal deposition (LMD) forming was proposed. CNTs were effective in increasing the laser absorptivity of the composite powder. Peak temperature and temperature field of LMD molten pool changed significantly. Realized the monolithic structures LMD-formation of CNTs/AlSi10Mg aluminum matrix nanocomposites. LMD processes facilitate the fabrication of metal matrix composites (CNTs/AlSi10Mg). Abstract: Recently, research of carbon nanotubes (CNTs) doping reinforced aluminum matrix nanocomposites has drawn significant attention. In this study, we conducted annular beam directed energy deposition (DED) experiments using CNTs/AlSi10Mg composites, prepared using a new procedure to improve the laser absorptivity of AlSi10Mg. The effect of the dispersant on CNTs adsorption and that of CNTs adsorption on temperature field, microstructure evolution, formability, and properties were clarified experimentally. The results show that CNTs exhibit good dispersion and adsorption in pure N-methyl pyrrolidone (NMP). Further, grains in the DED track were refined as the CNTs content increased, micro-hardness and laser absorptivity also improved. High-quality thin walls of 0.5- wt%-CNTs/AlSi10Mg were successfully formed, demonstrating that the new DED method for the preparation of CNTs/AlSi10Mg metal matrix nanocomposites is viable, expanding the potential application scenarios of composite material structures.